The Boxer Movement in China 1898–1901 (Journal of the College of Basic Education, 2022)
The Boxers movement is one of the most prominent revolutionary movements that China witnessed in the late imperial era. Its movement was affected by the country's internal situation and its external conditions, which were represented by the failure of reform attempts and the exacerbation of the volume of foreign intervention in it, especially after the Sino-Japanese War 1894-1895 and the division of the country into zones of international influence until it launched a number Among the foreign studies on this phenomenon is the title (splitting the watermelon).